The Delayed Ionospheric Response to the 27‐day Solar Rotation Period Analyzed With GOLD and IGS TEC Data. Issue 2 (7th February 2021) - Schmölter, Erik; Berdermann, Jens; Codrescu, Mihail
Abstract: The delayed ionospheric response is analyzed for two well‐defined 27‐day solar rotation periods in the year 2019 with solar radio flux index F10.7 and Global‐scale Observations of the Limb and Disk (GOLD) data, like solar extreme ultraviolet (EUV) flux proxy, O/N2 column density ratio and peak electron density, as well as International Global Navigation Satellite System Service rapid high‐rate total electron content (TEC) map data. Although the correlation between GOLD solar EUV flux proxy and TEC is similar to the correlation between F10.7 and TEC, it is shown that the estimated delays based on GOLD data are in much better agreement with recent studies using EUV measurements compared to the delays based on F10.7 data. The GOLD peak electron density correlates well with TEC and allows insight to a local time interval when the ionosphere is not controlled by solar activity changes (17:00 LT to 21:00 LT). The present study investigates the impact of the solar activity (F10.7, GOLD EUV flux proxy) and O/N2 column density ratio on the ionospheric delay for two representative solar rotation periods. The capabilities of GOLD data for future research on the ionospheric response to the 27‐day solar rotation period are demonstrated and discussed. These results are crucial information for precise ionospheric models and forecasts. Key Points: The good correlation of Global‐scale Observations of the Limb and Disk (GOLD) extreme ultraviolet (EUV) proxy and GOLD peak electron density with total electron content (TEC) allows detailed studies of the delayed ionospheric response The ionospheric delay to the 27‐day solar rotation period based on GOLD EUV proxy and TEC confirms recent delay estimates of about 1 day GOLD measurements at different times of the day allow insight into ionization, recombination and related accumulation processes